Analysis of Angklung Sound Intensity as a Acoustic Instrument - Rizka Silviana Hartanti; Budi Astuti (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2016)
The purpose of this study was to analysis of angklung sound intensity. The research method is using angklung musician 2 octaves. Each consists of two tube tone that sounded from the tone of G to G ', length and diameter of the tube every tone becomes independent variable, while intensity of the sound produced becomes dependent variable. Sound intensity is measured using a Sound Level Meter is placed with a constant distance. The result showed that G tone was a low tone which had a frequency of 49.5 Hz, first tube had 21.6 cm length and 4.1 cm diameter, second tube had 10.1 cm length and 3.4 cm diameter produced the sound intensity of 90.7 dB. G’ tone was a high tone which had a frequency of 99 Hz, first tube had 10 cm length and 3 cm diameter, second tube had 5.5 cm length and 2.1 cm diameter produced the sound intensity of 99.1 dB. It can be concluded that the higher the frequency, the greater the intensity of the sound produced. The shorter tube length and the smaller tube diameter, the greater the intensity of the sound. ©2016 JNSMR UIN Walisongo. All rights reserved.